Thermal Sensitivity and Sucrose Accumulation in Response to Chemical Ripener Application in Sugarcane - S. Venkataramana1,2, K. Shanmugaraja1*, M. Vigneeswaran1 and (Journal of Experimental Sciences, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Effect of two promising chemical ripeners (Ethrel and Glyphosate) was tested on the sucrose accumulation process of two popularly grown sugarcane varieties (Co 86032 and Co 94012) during maturity and ripening phase (240 days to 360 days). Invertase enzymes (acid and neutral invertase) responsible for sucrose accumulation, electrolyte leakage in relation to temperature, hormonal analysis through HPLC, sucrose % and Brix % of juice were studied in ethrel or glyphosate treated cane varieties. The acid and neutral invertases increased with moderate increase in temperature. However, 50 º C treatments were inhibitory for acid invertase particularly in Co 86032 at 360 days. At final harvest the sucrose% juice was 19.22% in Co 86032 and 21.98% in Co 94012. Ethrel has shown 0.7% improvement in Co 86032, while glyphosate treatment had shown 4.59% improvement in sucrose% juice.